(untitled) (Texas Journal of Medical Science, 2026)
This article aims to provide a comprehensive understanding of first aid measures for patients with open and closed fractures. Open fractures involve a break in the skin, exposing the bone, while closed fractures do not penetrate the skin. The importance of prompt and appropriate first aid cannot be overstated, as it significantly impacts the overall outcome of the patient. This article reviews the available literature, discusses various first aid techniques, and provides conclusions and suggestions for optimizing the initial response to fractures